The Effect of Sodium Silicate and Acrylic on Physical and Mechanical Parameters of Thatch Mortar - shayesteh namvar; Masoud Zeini (مسکن و محیط روستا)
In the past the earthen materials were accounted as the most widely used materials both structurally as well as finishing of traditional and historical buildings in urban and rural areas across the country. However, due to the wear and tear and lack of resistance to humidity and subjected loads, the roof and the walls covered with thatch mortars need to be annually reconstructed and repaired, which today is a serious maintained predicament. Low resistance against the lateral loads and cracking in walls, rapid erosion due to humidity, low-resistance against decay and impacts are major disadvantages of such mortars. Thus, durability of thatch as one of the stable and eco-friendly materials is very important.